Motor system abnormalities in hereditary spastic paraparesis type 4 (SPG4) depend on the type of mutation in the spastin gene. Issue 8 (21st July 2003) - Bönsch, D; Schwindt, A; Navratil, P; Palm, D; Neumann, C; Klimpe, S; Schickel, J; Hazan, J; Weiller, C; Deufel, T; Liepert, J
Abstract : Background: Hereditary spastic paraparesis (HSP) denotes a group of inherited neurological disorders with progressive lower limb spasticity as their clinical hallmark; a large proportion of autosomal dominant HSP belongs to HSP type 4, which has been linked to the SPG4 locus on chromosome 2. A variety of mutations have been identified within the SPG4 gene product, spastin. Objective: Correlation of genotype and electrophysiological phenotype. Material: Two large families with HSP linked to the SPG4 locus with a very similar disease with respect to age of onset, progression, and severity of symptoms. Methods: Mutation analysis was performed by PCR from genomic DNA and cDNA, and direct sequencing. The motor system was evaluated using transcranial magnetic stimulation. Results: Patients differ in several categories depending on the type of mutation present. Conclusions: For the first time in hereditary spastic paraparesis, a phenotypic correlate of a given genetic change in the spastin gene has been shown.